Insurance system for accidents and injuries in sports fields - قرماش وهيبة (sports creativity, 2025)
Due to the high rates of sports injuries and the exacerbation of their serriousness,it has become necessary to put in place laws and regulation and provide security and safety factors as preventive measures to reduce injury and as controls that put sports practice in the right context ,in addition to the medical and health procedures and measures that must be followed and the laws that regulate the game and provide the appropriate climate, insurance against injuries sports in one of the important means of insurance in the sports field,and from this point of view,our study aims to show hwo to compensate for damages that may be caused to sports practitioners through the insurance system for accidents and injuries in sports fields